Language-ing the Earth: Experiential Renewal for a Relationally Sensitive Environmentalism - Patrick Howard (University of Alberta, 2021)
This paper investigates human relationship with the larger living landscape that is grounded in experiential renewal. Phenomenology is antithesis to the process of abstraction and objectification through which the world as we experience it is diminished by conceptualization and categorization. Recent studies to understand the natural world as a hermeneutic text offers important reflections on the human mediation of the meaning of the more-than-human-world and assists in understanding the implications of our encounters with the world. Phenomenology, however, is unique in its capacity to bring to expression, rather than silencing, our relationship with the natural world and our human inherency in it. This paper explores phenomenologically sensate reciprocity as it is encountered in lived experience. Through deepening our attunement for our embodied integration in a living world we may relearn and restore a capacity to dwell more thoughtfully with newfound sensitivity, respect, and restraint in the ecosystems on which we wholly depend.